The UTHM SUKSIS Fingerprint Voting System - Anisa, Adibah; Ruhaya Ab. Aziz (Applied Information Technology And Computer Science, 2023)
UTHM SUKSIS Fingerprint Voting System is an application that will be used by SUKSIS trainees on election day to form the new highest council. It was developed because the election method used now is less systematic. There are three objectives of this system which are to analyze and design the UTHM SUKSIS Fingerprint Voting System, to develop a UTHM SUKSIS Fingerprint Voting System, and to test the UTHM SUKSIS Fingerprint Voting System. The waterfall model is used to ensure that the system is thoroughly analyzed before development begins. The result of this system is a system that has full transparency and has reliable processes.